Particle distributions and dynamics in the euphotic zone of the North Pacific Subtropical Gyre. Issue 5 (3rd May 2015) - Barone, Benedetto; Bidigare, Robert R.; Church, Matthew J.; Karl, David M.; Letelier, Ricardo M.; White, Angelicque E.
Abstract During the summer of 2012, we used laser diffractometry to investigate the temporal and vertical variability of the particle size spectrum (1.25–100 µm in equivalent diameter) in the euphotic zone of the North Pacific Subtropical Gyre. Particles measured with this optical method accounted for ∼40% of the particulate carbon stocks (<202 µm) in the upper euphotic zone (25–75 m), as estimated using an empirical formula to transform particle volume to carbon concentrations. Over the entire vertical layer considered (20–180 m), the largest contribution to particle volume corresponded to particles between 3 and 10 µm in diameter. Although the exponent of a power law parameterization suggested that larger particles had a lower relative abundance than in other regions of the global ocean, this parameter and hence conclusions about relative particle abundance are sensitive to the shape of the size distribution and to the curve fitting method. Results on the vertical distribution of particles indicate that different size fractions varied independently with depth. Particles between 1.25 and 2 µm reached maximal abundances coincident with the depth of the chlorophyll a maximum (averaging 121 ± 10 m), where eukaryotic phytoplankton abundances increased. In contrast, particles between 2 and 20 µm tended to accumulate just below the base of the mixed layer (41 ± 14 m). Variability in particle size tracked changes in the abundance of specific photoautotrophic organisms (measured with flow cytometry and pigment concentration), suggesting that phytoplankton population dynamics are an important control of the spatiotemporal variability in particle concentration in this ecosystem.